Manufacturing method of rubber molded products
By adding a plasticizer to form a paste-like mixture through wet grinding with vulcanizing agents or accelerators, the method improves dispersion and reduces defects in rubber compositions, enhancing productivity.
Patent Information
- Application Number
- JP2020189105
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-11-13
- Publication Date
- 2025-02-06
- Estimated Expiration
- 2040-11-13
AI Technical Summary
Existing methods for producing rubber compositions with highly cohesive vulcanization accelerators result in poor dispersion, leading to defects such as bubbles, scratches, and residual compounding agents, and are limited by the melting point of these compounds, affecting productivity.
A method involving the addition of a plasticizer to form a paste-like mixture through wet grinding with vulcanizing agents or accelerators, followed by kneading with rubber, to improve dispersion and reduce defects.
The method significantly reduces defects like bubbles, scratches, and residual compounding agents, enhancing the productivity of rubber molded products.
Smart Images

Figure 0007627479000001 
Figure 0007627479000002 
Figure 0007627479000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a rubber composition, and also to a method for producing a molded rubber article obtained by vulcanizing the rubber composition. [Background technology]
[0002] Among compounding agents such as vulcanization accelerators added to rubber compositions, those with high coagulation properties are known. When such vulcanization accelerators with high coagulation properties are kneaded with rubber, there is a problem that they are poorly dispersed, causing defects such as residual compounding agents in the rubber molded product obtained by molding. Patent Document 1 describes a method for improving such poor dispersion by adding a plasticizer to a guanidine compound, melting the guanidine, and then forming it into a paste to prepare a vulcanization accelerator. According to this method, it is said that defects caused by poor dispersion of the vulcanization accelerator can be completely prevented in the kneading process, molding process, etc. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2002-309040 A Summary of the Invention [Problem to be solved by the invention]
[0004] However, in Patent Document 1, the guanidine compound is melted at a high temperature equal to or higher than the melting point thereof, which causes problems in productivity and makes it impossible to apply the method to compounding ingredients that are difficult to melt. Thus, there has been a demand for a method for producing a rubber composition that can solve these problems.
[0005] The present invention has been made to solve the above problems, and has an object to provide a method for producing a rubber composition with excellent productivity, which can produce rubber molded products in which defects such as air bubbles, scratches, and residual compounding ingredients due to poor dispersion are significantly reduced. [Means for solving the problem]
[0006] The above-mentioned problem is solved by providing a method for producing a rubber composition, the method comprising: a wet-grinding step of adding a plasticizer to at least one powder material selected from the group consisting of a vulcanizing agent and a vulcanization accelerator, and subjecting the resulting mixture to wet-grinding to obtain a paste-like mixture; and a kneading step of kneading at least rubber with the paste-like mixture to obtain a rubber composition.
[0007] At this time, it is preferable that the blending ratio of the powder material and the plasticizer in the paste-like mixture is 1:0.5 to 1:20. It is a preferable embodiment that 0.1 to 100 parts by mass of the paste-like mixture is blended with 100 parts by mass of the rubber. It is preferable that the rubber is at least one selected from the group consisting of chloroprene rubber (CR), nitrile rubber (NBR), hydrogenated nitrile rubber (HNBR), ethylene propylene rubber (EPDM), acrylic rubber (ACM), ethylene acrylic rubber (AEM) and fluororubber (FKM), it is preferable that the vulcanizing agent is at least one selected from the group consisting of sulfur and amine-based vulcanizing agents, and it is preferable that the vulcanization accelerator is at least one selected from the group consisting of thiuram-based vulcanization accelerators, guanidine-based vulcanization accelerators, dithiocarbamate-based vulcanization accelerators and thiazole-based vulcanization accelerators. It is preferable that the maximum particle size of the particles contained in the pasty mixture is 80 μm or less, and the average particle size of the particles contained in the pasty mixture is 0.1 to 30 μm.
[0008] In the kneading step, a second plasticizer is further added and kneaded, and in the method for producing a rubber molded product, the method includes a vulcanization step of vulcanizing the rubber composition obtained in the kneading step. In another preferred embodiment, the rubber molded product is a sealing member. Effect of the Invention
[0009] According to the present invention, a method for producing a rubber composition with excellent productivity can be provided, which can produce a rubber molded product in which defects such as air bubbles, scratches, and residual compounding ingredients due to poor dispersion are significantly reduced. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] The present invention is a method for producing a rubber composition, comprising a wet-grinding step (hereinafter sometimes abbreviated as "wet-grinding step") of obtaining a paste-like mixture by adding a plasticizer (hereinafter sometimes referred to as "first plasticizer") to at least one powder material selected from the group consisting of vulcanizing agents and vulcanization accelerators and wet-grinding the mixture, and a kneading step (hereinafter sometimes abbreviated as "kneading step") of kneading at least rubber with the paste-like mixture to obtain a rubber composition.
[0011] As can be seen from the comparison between the examples and the comparative examples described later, in the comparative examples in which the rubber was kneaded with a powder of a vulcanizing agent or a vulcanization accelerator, the defect rate (%) due to poor dispersion was above a certain level, and defects such as air bubbles, scratches, and residual compounding agents were observed in the obtained rubber molded product. In contrast, in the examples in which a wet grinding process was adopted, the defect rate (%) due to poor dispersion was 0%, and defects such as air bubbles, scratches, and residual compounding agents were not observed in the obtained rubber molded product. That is, by adopting a wet grinding process in which a plasticizer is added to at least one powder material selected from the group consisting of a vulcanizing agent and a vulcanization accelerator and the wet grinding process is performed to obtain a paste-like mixture, it has become clear that a rubber molded product in which the dispersibility is improved in the kneading process in which the rubber and the paste-like mixture are kneaded to obtain a rubber composition can be provided with a significantly reduced number of defects such as air bubbles, scratches, and residual compounding agents due to poor dispersion can be provided. In this way, it can be seen that the significance of the present invention is great because the adoption of the wet grinding process makes it possible to obtain a paste-like mixture with good productivity without melting the powder material even when the melting point of the powder material is very high. In this specification, "bubbles, scratches, and residual compounding agents" are caused by at least one compounding agent selected from the group consisting of vulcanizing agents and vulcanization accelerators.
[0012] The powder material used in the present invention is at least one selected from the group consisting of vulcanizing agents and vulcanization accelerators. The vulcanizing agent used in the present invention is not particularly limited, but is preferably at least one selected from the group consisting of sulfur and amine-based vulcanizing agents such as hexamethylenediamine carbamate (HMDC). The vulcanization accelerator used in the present invention is not particularly limited, and includes thiuram-based vulcanization accelerators such as tetramethylthiuram disulfide; guanidine-based vulcanization accelerators such as 1,3-di-o-tolylguanidine; dithiocarbamate-based vulcanization accelerators such as zinc dibutyldithiocarbamate; and thiazole-based vulcanization accelerators such as 2-mercaptobenzothiazole. The vulcanization accelerator is preferably at least one selected from the group consisting of thiuram-based vulcanization accelerators, guanidine-based vulcanization accelerators, dithiocarbamate-based vulcanization accelerators, and thiazole-based vulcanization accelerators. In a preferred embodiment, the powder material used in the wet grinding process is made up of only a vulcanizing agent, and among these, hexamethylenediamine carbamate (HMDC) is preferably used.
[0013] The plasticizer used in the present invention is not particularly limited as long as it is compounded with rubber, and examples thereof include phthalic acid-based plasticizers such as dioctyl phthalate, adipic acid-based plasticizers such as dioctyl adipate, sebacic acid-based plasticizers such as dibutyl sebacate, trimellitic acid-based plasticizers such as trimethyl trimellitate, polyester-based plasticizers such as adipic acid polyester and phthalic acid polyester, polyether ester-based plasticizers such as phthalic acid ether ester and adipic acid ether ester, phosphoric acid-based plasticizers such as trioctyl phosphate, and petroleum-based hydrocarbons. These plasticizers can be used alone or in combination of two or more. Among them, at least one plasticizer selected from the group consisting of phthalic acid-based plasticizers, adipic acid-based plasticizers, polyester-based plasticizers, polyether ester-based plasticizers, and phosphoric acid-based plasticizers is preferably used.
[0014] In the wet grinding step of the present invention, the plasticizer is added to the powder material and the mixture is wet-ground to obtain a paste-like mixture. As an apparatus used for the wet grinding, a known wet grinding apparatus such as a ball mill, a bead mill, a mortar mill, a jet mill, etc. can be used. The blending ratio (mass ratio) of the powder material to the plasticizer is preferably 1:0.5 to 1:20. The blending ratio is more preferably 1:1 to 1:18, and further preferably 1:1.5 to 1:15.
[0015] In the present invention, a preferred embodiment is that the maximum particle size of the particles contained in the paste-like mixture is 80 μm or less. If the maximum particle size exceeds 80 μm, the resulting rubber molded product may have defects such as air bubbles, scratches, and residual compounding agents due to poor dispersion, so the maximum particle size is more preferably 70 μm or less, even more preferably 40 μm or less, and particularly preferably 30 μm or less. The maximum particle size of the particles contained in the paste-like mixture is usually 3 μm or more. The maximum particle size in this specification is the value indicating the largest maximum particle size in the volume-based particle size distribution.
[0016] In the present invention, the average particle diameter of the particles contained in the paste-like mixture is preferably 0.1 to 30 μm. If the average particle diameter is less than 0.1 μm, it may take a long time to prepare the paste-like mixture, and the average particle diameter is more preferably 0.5 μm or more, even more preferably 1 μm or more, and particularly preferably 1.5 μm or more. On the other hand, if the average particle diameter exceeds 30 μm, there is a risk that defects such as air bubbles, scratches, and residual compounding agents due to poor dispersion may occur in the obtained rubber molded product, and the average particle diameter is more preferably 20 μm or less, even more preferably 15 μm or less, and particularly preferably 12 μm or less. The average particle diameter in this specification is the particle diameter when the volume-based integrated value determined based on the volume-based particle size distribution is 50%.
[0017] In the present invention, after the wet grinding step, a kneading step is performed in which at least rubber and the paste-like mixture are kneaded to obtain a rubber composition. The rubber used in the kneading step is not particularly limited, and examples thereof include chloroprene rubber (CR); nitrile rubber (NBR) and hydrogenated nitrile rubber (HNBR); ethylene propylene rubber (EPDM); acrylic rubber (ACM), ethylene acrylic rubber (AEM), and other acrylic rubbers; and fluororubber (FKM). Among these, at least one selected from the group consisting of chloroprene rubber (CR), nitrile rubber (NBR), hydrogenated nitrile rubber (HNBR), ethylene propylene rubber (EPDM), acrylic rubber (ACM), ethylene acrylic rubber (AEM), and fluororubber (FKM) is preferable, and at least one selected from the group consisting of nitrile rubber (NBR), hydrogenated nitrile rubber (HNBR), acrylic rubber (ACM), and ethylene acrylic rubber (AEM) is more preferable.
[0018] The chloroprene rubber (CR) is not particularly limited, and may be any rubber containing 2-chloro-1,3-butadiene as the main component. 2-chloro-1,3-butadiene may be polymerized alone, or 2-chloro-1,3-butadiene may be copolymerized with other monomers. As the other monomers, acrylic esters such as methyl acrylate, ethyl acrylate, butyl acrylate, and methoxyethyl acrylate are preferably used.
[0019] The nitrile rubber is not particularly limited, and a copolymer of acrylonitrile and 1,3-butadiene can be used. Hydrogenation of the double bonds remaining in the 1,3-butadiene units after polymerization is optional. Non-hydrogenated nitrile rubber (NBR) and hydrogenated nitrile rubber (HNBR) can be preferably used. The content of acrylonitrile units in the nitrile rubber is preferably 15 to 50% by mass. As long as it does not impair the effects of the present invention, it may contain structural units derived from other copolymerizable monomers, but the content is usually 10% by mass or less, and preferably 5% by mass or less.
[0020] The ethylene propylene rubber (EPDM) is not particularly limited, and a copolymer of ethylene, propylene, and a diene compound can be used. Examples of diene compounds contained in EPDM include ethylidene norbornene (ENB), 1,4-hexadiene, and dicyclopentadiene. As long as the effects of the present invention are not impaired, structural units derived from other copolymerizable monomers may be contained, but the content is usually 10% by mass or less, and preferably 5% by mass or less.
[0021] The acrylic rubber is not particularly limited, and may be any rubber containing an acrylic acid ester as a main component. As the acrylic acid ester, methyl acrylate, ethyl acrylate, butyl acrylate, methoxyethyl acrylate, etc. are preferably used. As the monomer to be copolymerized with the acrylic acid ester, acrylonitrile, ethylene, etc. are exemplified. Specifically, acrylic rubber (ACM) obtained by copolymerizing two or more acrylic acid esters selected from methyl acrylate, ethyl acrylate, butyl acrylate, and methoxyethyl acrylate and a crosslinkable monomer, and acrylic rubber (AEM) obtained by copolymerizing methyl acrylate, ethylene, and a crosslinkable monomer are preferably used. As the AEM, "VAMAC" (registered trademark) from DuPont, etc. are available. As long as it does not impede the purpose of the present invention, it may contain a constituent unit derived from another copolymerizable monomer, but the content is usually 10% by mass or less, preferably 5% by mass or less.
[0022] The fluororubber (FKM) is not particularly limited, and examples thereof include copolymers of vinylidene fluoride (VDF) and hexafluoropropylene (HFP), copolymers of VDF and trichlorofluoroethylene (CTFE), copolymers of VDF, HFP and tetrafluoroethylene (TFE), copolymers of TFE and propylene, copolymers of TFE and fluorine-containing vinyl ether, and copolymers of hydrocarbon-based diene monomers and fluorine-containing monomers. Among these, ternary fluororubbers, which are copolymers of VDF, HFP and tetrafluoroethylene (TFE), are preferably used. As long as the effects of the present invention are not impaired, they may contain structural units derived from other copolymerizable monomers, but the content is usually 10% by mass or less, preferably 5% by mass or less.
[0023] In the kneading step, it is a preferred embodiment that 0.1 to 100 parts by mass of the paste-like mixture is blended with respect to 100 parts by mass of the rubber. If the blending amount is less than 0.1 parts by mass, the performance of the vulcanizing agent or vulcanization accelerator may not be exhibited, so it is more preferably 0.2 parts by mass or more, even more preferably 0.5 parts by mass or more, and particularly preferably 0.8 parts by mass or more. On the other hand, if the blending amount exceeds 100 parts by mass, the vulcanization may proceed too quickly, so it is more preferably 80 parts by mass or less, even more preferably 60 parts by mass or less, and particularly preferably 40 parts by mass or less.
[0024] In the kneading step, the method for kneading the rubber and the paste-like mixture is not particularly limited, but they can be kneaded using a roll, a kneader, a Banbury mixer, an intermix, an extruder, etc. The temperature of the rubber composition during kneading is preferably 20 to 170°C.
[0025] In the kneading step, it is a preferred embodiment to compound fillers such as white fillers and carbon black. The white fillers used in the present invention are not particularly limited, and silica, clay, calcium carbonate, diatomaceous earth, wollastonite, etc. can be used. The carbon black used in the present invention is not particularly limited, and FEF, SRF, SAF, ISAF, HAF, MAF, GPF, FT, MT, etc. can be used. The amount of the white filler or carbon black compounded is preferably 1 to 200 parts by mass, more preferably 10 to 90 parts by mass, based on 100 parts by mass of the rubber.
[0026] In the kneading step, it is also a suitable embodiment to further add and knead a second plasticizer. The total amount of the first plasticizer and the second plasticizer is preferably 1 to 100 parts by mass relative to 100 parts by mass of the rubber. The second plasticizer may be the same as the first plasticizer used in the wet grinding step, or may be different. In this embodiment, the required amount of plasticizer relative to 100 parts by mass of rubber is mixed twice as the first plasticizer and the second plasticizer, but in the wet grinding step, a paste-like mixture may be obtained by adding a required amount of plasticizer to the powder material and performing wet grinding. In this case, the second plasticizer does not need to be added in the kneading step.
[0027] In the kneading step, various compounding agents that are commonly used in rubber compositions, such as vulcanization aids, antioxidants, processing aids, acid acceptors, colorants, and fillers, may be included within the range that does not impair the effects of the present invention.
[0028] A rubber molded product can be suitably obtained by carrying out a vulcanization step in which the rubber composition obtained in the kneading step is vulcanized. In the vulcanization step, the rubber composition is molded into a desired shape, and a crosslinking reaction (vulcanization) proceeds by heating. Examples of a molding method for the rubber composition include injection molding and compression molding. The crosslinking temperature is usually 100 to 250°C. The crosslinking time is usually 0.5 minutes to 24 hours. Secondary crosslinking may be carried out by further heating.
[0029] The rubber molded product obtained by the present invention is preferably a sealing member. Suitable sealing members include packing, seals, gaskets, O-rings, and diaphragms. Specifically, examples of the seal include bearing seals and oil seals, and examples of the gasket include intake manifold gaskets and head cover gaskets. EXAMPLES
[0030] below Comparative Example 4 The raw materials used in Comparative Example 1 are as follows. [Raw materials] Nitrile rubber (NBR): "Nipol 1042" manufactured by Zeon Corporation Carbon black: "Seast 3 (HAF)" manufactured by Tokai Carbon Co., Ltd. Plasticizer: "DOP" manufactured by ADEKA Corporation Processing aid: Stearic acid manufactured by J-Plus Co., Ltd. Zinc oxide: "ZINCA#20" manufactured by Sakai Chemical Industry Co., Ltd. Vulcanizing agent: Hosoi Chemical Industry's "Fine Sulfur 500Mesh" - Vulcanization accelerator: "ACCEL PZ" zinc dimethyldithiocarbamate manufactured by Kawaguchi Chemical Industry Co., Ltd.
[0031] Comparative Example 4 0.5 parts by mass of plasticizer and 0.5 parts by mass of vulcanizing agent powder (average particle size: 50 μm, maximum particle size: 175 μm) were put into a wet grinding device, and wet grinding treatment was performed at room temperature for 1 hour to obtain a paste-like mixture. When the particle size of the particles contained in the paste-like mixture was measured using a particle size distribution measuring device "LA-950" manufactured by Horiba, Ltd., the average particle size was 15 μm and the maximum particle size was 70 μm. With respect to 100 parts by mass of nitrile rubber (NBR), 1 part by mass of the paste-like mixture, 65 parts by mass of carbon black, 14.5 parts by mass of plasticizer, 1 part by mass of processing aid, 5 parts by mass of zinc oxide, and 0.3 parts by mass of vulcanization accelerator were kneaded using an open roll at 70 ° C. to prepare an unvulcanized rubber material. The obtained unvulcanized rubber material was vulcanized and molded at 170 ° C. for 10 minutes using an injection molding machine to obtain a molded product, a gasket. The obtained gaskets were observed under a magnifying glass, and the percentage of defects (%) due to poor dispersion was calculated. The percentage of defects (%) due to poor dispersion is expressed as the ratio of the number of molded products that were confirmed to have defects (air bubbles, scratches, residual compounding agent) to the total number of molded products. The results are summarized in Table 1.
[0032] Comparative Example 1 Comparative Example 4 Instead of obtaining a paste-like mixture, 100 parts by mass of nitrile rubber (NBR) was mixed with 0.5 parts by mass of a vulcanizing agent powder (average particle size: 50 μm, maximum particle size: 175 μm), 65 parts by mass of carbon black, 15 parts by mass of a plasticizer, 1 part by mass of a processing aid, 5 parts by mass of zinc oxide, and 0.3 parts by mass of a vulcanization accelerator at 70° C. using an open roll. Comparative Example 4 In the same manner as above, a molded gasket was obtained. Comparative Example 4 The gaskets obtained were observed under a magnifying glass in the same manner as in the above, and the defective rate (%) due to poor dispersion was calculated. The results are shown in Table 1.
[0033] [Table 1]
[0034] The raw materials used in the following Example 2 and Comparative Example 2 are as follows. [Raw materials] Acrylic rubber (ACM): ZEON Corporation "AR12" Carbon black: "Seast 3 (HAF)" manufactured by Tokai Carbon Co., Ltd. Plasticizer: Adeka Cizer RS1000 manufactured by ADEKA Corporation Processing aid A: NOF Corporation "Stearic acid" Processing aid B: NI Chemitech Co., Ltd. "Greg G8205" Anti-aging agent: "Nauguard 445" manufactured by Shiraishi Calcium Co., Ltd. Vulcanization accelerator: Ouchi Shinko Chemical Industry Co., Ltd. "Noccela DT" 1,3-di-o-tolyl guanidine Vulcanizing agent: Chemours Corporation's "Diak No. 1" hexamethylenediamine carbamate (HMDC)
[0035] Example 2 A paste-like mixture was obtained by putting 2 parts by mass of plasticizer and 0.5 parts by mass of vulcanizing agent powder (average particle size: 50 μm, maximum particle size: 500 μm) into a wet grinding device and performing wet grinding at room temperature for 1 hour. When the particle size of the particles contained in the paste-like mixture was measured using a particle size distribution measuring device "LA-950" manufactured by Horiba, Ltd., the average particle size was 3 μm and the maximum particle size was 25 μm. With respect to 100 parts by mass of acrylic rubber (ACM), 2.5 parts by mass of the paste-like mixture, 60 parts by mass of carbon black, 8 parts by mass of plasticizer, 1 part by mass each of processing aids a and b, 1 part by mass of antioxidant, and 2.0 parts by mass of vulcanization accelerator were kneaded using an open roll at 70 ° C. to prepare an unvulcanized rubber material. The obtained unvulcanized rubber material was vulcanized and molded at 170 ° C. for 10 minutes using an injection molding machine to obtain a molded product, a gasket. Comparative Example 4 The gaskets obtained were observed under a magnifying glass in the same manner as in the above, and the percentage of defective products (%) due to poor dispersion was calculated. The results are shown in Table 2.
[0036] Comparative Example 2 In Example 2, instead of obtaining a paste-like mixture, 100 parts by mass of acrylic rubber (ACM) was kneaded with 0.5 parts by mass of vulcanizing agent powder (average particle size: 50 μm, maximum particle size: 500 μm), 60 parts by mass of carbon black, 10 parts by mass of plasticizer, 1 part by mass each of processing aids a and b, 1 part by mass of antioxidant, and 2.0 parts by mass of vulcanization accelerator at 70°C using an open roll to obtain a molded gasket in the same manner as in Example 2. Comparative Example 4 The gaskets obtained were observed under a magnifying glass in the same manner as in the above, and the percentage of defective products (%) due to poor dispersion was calculated. The results are shown in Table 2.
[0037] [Table 2]
[0038] below Comparative Example 5 The raw materials used in Comparative Example 3 are as follows. [Raw materials] Acrylic rubber (ACM): ZEON Corporation "AR51" Carbon black: "Seast 3 (HAF)" manufactured by Tokai Carbon Co., Ltd. Plasticizer: Adeka Cizer RS1000 manufactured by ADEKA Corporation Processing aid A: NOF Corporation "Stearic acid" Processing aid B: NI Chemitech Co., Ltd. "Greg G8205" Anti-aging agent: "Nauguard 445" manufactured by Shiraishi Calcium Co., Ltd. Vulcanization accelerator a: "Noccela PZ" zinc dimethyldithiocarbamate manufactured by Ouchi Shinko Chemical Industry Co., Ltd. Vulcanization accelerator B: "Noccela TTFE" ferric dimethyldithiocarbamate manufactured by Ouchi Shinko Chemical Industry Co., Ltd. Vulcanizing agent: LANXESS "Bulcurrent E / C" N-phenyl-N-(trichloromethylsulfenyl)benzenesulfonamide
[0039] Comparative Example 5 2.5 parts by mass of plasticizer and 2.5 parts by mass of vulcanization accelerator a powder (average particle size: 40 μm, maximum particle size: 300 μm) were placed in a wet grinding device, and wet grinding treatment was performed at room temperature for 1 hour to obtain a paste-like mixture. When the particle size of the particles contained in the paste-like mixture was measured using a particle size distribution measuring device "LA-950" manufactured by Horiba, Ltd., the average particle size was 20 μm and the maximum particle size was 70 μm. With respect to 100 parts by mass of acrylic rubber (ACM), 5 parts by mass of the paste-like mixture, 50 parts by mass of carbon black, 12.5 parts by mass of plasticizer, 1 part by mass each of processing aids a and b, 2 parts by mass of antioxidant, 0.5 parts by mass of vulcanization accelerator b, and 0.5 parts by mass of vulcanizing agent were kneaded using an open roll at 70 ° C. to prepare an unvulcanized rubber material. The resulting unvulcanized rubber material was vulcanized at 170°C for 10 minutes using an injection molding machine and molded into a molded product, a gasket. Comparative Example 4 The gaskets obtained were observed under a magnifying glass in the same manner as in the above, and the defective rate (%) due to poor dispersion was calculated. The results are shown in Table 3.
[0040] Comparative Example 3 Comparative Example 5 Instead of obtaining a paste-like mixture, 100 parts by mass of acrylic rubber (ACM) was kneaded with 2.5 parts by mass of vulcanization accelerator a powder (average particle size: 40 μm, maximum particle size: 300 μm), 50 parts by mass of carbon black, 15 parts by mass of plasticizer, 1 part by mass each of processing aids a and b, 2 parts by mass of antioxidant, 0.5 parts by mass of vulcanization accelerator b, and 0.5 parts by mass of vulcanizing agent at 70°C using an open roll. Comparative Example 5 In the same manner as above, a molded gasket was obtained. Comparative Example 4 The gaskets obtained were observed under a magnifying glass in the same manner as in the above, and the defective rate (%) due to poor dispersion was calculated. The results are shown in Table 3.
[0041] [Table 3]
Claims
1. A method for producing a rubber molded product, comprising a vulcanization step of vulcanizing a rubber composition, The rubber composition is obtained by a wet grinding process in which a powder material consisting of only an amine-based vulcanizing agent is added with a plasticizer and then wet-ground to obtain a paste-like mixture, and a kneading process in which at least rubber is kneaded with the paste-like mixture, The particles contained in the paste-like mixture have a maximum particle size of 30 μm or less, and an average particle size of the particles contained in the paste-like mixture is 0.1 to 12 μm; The method for producing a rubber molded product, wherein the rubber molded product is a sealing member.
2. 2. The method for producing a rubber molded product according to claim 1, wherein a compounding ratio of said powder material to said plasticizer in said paste-like mixture is 1:0.5 to 1:
20.
3. The method for producing a rubber molded product according to claim 1 or 2, wherein 0.1 to 100 parts by mass of the paste-like mixture is mixed with 100 parts by mass of the rubber.
4. The method for producing a rubber molded product according to any one of claims 1 to 3, wherein the rubber is at least one selected from the group consisting of chloroprene rubber (CR), nitrile rubber (NBR), hydrogenated nitrile rubber (HNBR), ethylene propylene rubber (EPDM), acrylic rubber (ACM), ethylene acrylic rubber (AEM) and fluororubber (FKM).
5. 5. The method for producing a rubber molded article according to claim 1, wherein a second plasticizer is further added and kneaded in the kneading step.
Citation Information
Patent Citations
Granular vulcanization accelerator for rubber
JP1989229055A
Vulcanizable composition of nitrile rubber
JP1994322183A
Chemical preparation of rubber
JP1995196853A
Method for preparing vulcanization promoter
JP2002309040A
Foamed molding
JP2006045329A